Peran Balai Pemasyarakatan (BAPAS) Kelas II Kupang dalam Melaksanakan Bimbingan dan Pembinaan Bagi Anak yang Berkonflik dengan Hukum - Yoseph Ruma Toli; Reny Rebeka Masu; A. Resopjiani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research analyzes the role of the Kupang Class II Correctional Center (BAPAS) in guiding and developing children in conflict with the law. Using an empirical legal method, the study relies on primary and secondary data. The issue of juvenile delinquency in Indonesia is escalating, with 1,885 cases reported in 2018 and 1,098 in 2020. Notably, children are involved in physical violence (58 cases), sexual violence (44 cases), and theft (22 cases). This highlights the urgent need for institutions like BAPAS to support, develop, and supervise these children. The research addresses two main questions: (1) What is the role of BAPAS in guiding and mentoring children in conflict with the law? and (2) What challenges does BAPAS face in the juvenile justice system? The findings reveal that BAPAS's role is divided into three stages: (a) pre-adjudication guidance and development, (b) support during the trial process (adjudication), and (c) assistance post-trial. BAPAS encounters challenges primarily related to the families of the children, as well as difficulties faced by community guidance officers in providing effective assistance. It is crucial for BAPAS to develop persuasive communication skills to engage families and encourage active participation in the rehabilitation process. This includes involvement in training and understanding the community's role in supporting children in conflict with the law.